The role of patient involvement in the promotion of hand hygiene amongst nurses in hospital settings: a qualitative study of nurses’ and patients’ experiences - Alzyood, Mamdooh; Jackson, Debra; Brooke, Joanne; Aveyard, Helen (International Journal of Infection Control, 2022)
Background: To date, there is a wealth of evidence that patients have been invited to take an active role in prompting hand hygiene of hospital staff, but there is insufficient evidence on what happens in practice and whether this is acceptable to both staff and patients. Objective: To understand the role of patient involvement in the promotion of hand hygiene amongst nurses in the hospital setting. Methods: This qualitative interpretive study comprised of focus group discussions conducted with nurses (n = 36) and interviews with patients (n = 21). Data from nurses were analysed using inductive thematic analysis. Data from patients were analysed by critical incident analysis. Results: Experiences from nurses and patients can be summarised into four themes: 1) both nurses and patients acknowledged the patients’ right to ask, 2) both groups reported concerns that asking about hand hygiene could have an adverse impact on the nurse–patient relationship, 3) patients reported negative reactions from nurses when promoting hand hygiene and 4) patients reported that the promotion of hand hygiene was not only offensive and upsetting for nurses but also embarrassing for patients. Conclusions: Findings from this study suggest that patients are expected to adopt a passive role in infection control and remain silent when observing non-compliance to hand hygiene within the hospital setting, to avoid being embarrassed, offensive and upsetting nurses.